Enhanced CRISPR/Cas9‐mediated biallelic genome targeting with dual surrogate reporter‐integrated donors. Issue 6 (8th March 2017) - Wu, Yun; Xu, Kun; Ren, Chonghua; Li, Xinyi; Lv, Huijiao; Han, Furong; Wei, Zehui; Wang, Xin; Zhang, Zhiying
Abstract : The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein 9 (Cas9) system has recently emerged as a simple, yet powerful genome engineering tool, which has been widely used for genome modification in various organisms and cell types. However, screening biallelic genome‐modified cells is often time‐consuming and technically challenging. In this study, we incorporated two different surrogate reporter cassettes into paired donor plasmids, which were used as both the surrogate reporters and the knock‐in donors. By applying our dual surrogate reporter‐integrated donor system, we demonstrate high frequency of CRISPR/Cas9‐mediated biallelic genome integration in both human HEK293T and porcine PK15 cells (34.09% and 18.18%, respectively). Our work provides a powerful genetic tool for assisting the selection and enrichment of cells with targeted biallelic genome modification. Abstract :